Optimization of quantum cascade laser operation by geometric design of cascade active band in open and closed models - Tkach, M.V.; Seti, Ju.O.; Boyko, I.V.; Voitsekhivska, O.M. (Condensed Matter Physics, 2013)
Using the effective mass and rectangular potential approximations, the theory of electron dynamic conductivity is developed for the plane multilayer resonance tunnel structure placed into a constant electric field within the model of open nanosystem, and oscillator forces of quantum transitions within the model of closed nanosystem. For the experimentally produced quantum cascade laser with four-barrier active band of separate cascade, it is proven that just the theory of dynamic conductivity in the model of open cascade most adequately describes the radiation of high frequency electromagnetic field while the electrons transport through the resonance tunnel structure driven by a constant electric field. У наближеннi ефективних мас i прямокутних потенцiалiв розвинута теорiя електронної динамiчної провiдностi плоскої багатошарової резонансно-тунельної структури у постiйному електричному полi в моделi вiдкритої наносистеми та сил осциляторiв квантових переходiв у моделi закритої системи. На прикладi експериментально реалiзованого квантового каскадного лазера з чотирибар’єрною активною зоною окремого каскаду показано, що саме теорiя динамiчної провiдностi у моделi вiдкритого каскаду найбiльш адекватно описує процес випромiнювання високочастотного електромагнiтного поля при проходженнi електронiв крiзь резонансно-тунельну структуру у постiйному електричному полi.